A tourist catwalk: the pedestrianisation of Rua das Portas de Santo Antão, Lisbon - Ramos, M. (Everyday Streets: Inclusive approaches to understanding and designing streets. Edited by: Agustina Martire, Jane Clossick and Birgit Hausleitner. UCL Press, 2022)
The unassuming Rua das Portas de Santo Antão, in downtown Lisbon, was once the unlikely epicentre of the city. During the years of the authoritarian regime of Estado Novo , it fell into progressive decline. Its partial pedestrianization in 1994 didn’t revive it but rather helped sanitise it and empty it to make way for the influx of international tourists. This chapter details the steps through which a de-gentrified street ended up being touristified, and how the rehabilitation of its heritage and the success that are its present conditions of walkability and liveability failed to connect with the city’s dwellers.